Biochemical blood profile of red deer (Cervus elaphus), reared in the conditions of Polissya Volyn - R. Hunchak (Біологія тварин)
It was found that the biochemical parameters of blood of red deer (Cervus elaphus) reared in the conditions of Polissya Volyn, in general, correspond to the main patterns characteristic of this population, although they have some fluctuations. Thus, we have shown that the content of total protein, its fractional composition, concentration of glucose, urea and creatinine in the blood serum of English deer blood line and Latvian crossbreed deer were within the reference values characteristic of this species of wildlife. It was found that the activity of ALT and GGT was higher in animals of English origin, and AST and ALP — in Latvian crossbred deer. The content of Ca, P, Mg and Na ions in the blood was also higher, respectively, by 9.4, 28, 22.7 and 4%. It was found that against the background of stress caused by physical method of capturing animals for blood sampling, the level of total protein and its albumin fraction. The concentration of urea was by 22.5%, glucose — by 18.4% and creatinine by 6.5% higher than in the group of animals with sedation. Under technological stress in deer, the activity of ALT and AST in the blood increases (by 11 and 5.5%) and ALP and GGT (by 9.1 and 20.0%), respectively. The study of blood biochemical parameters in young animals (3–4 months old) revealed that the content of total protein in females is 6.4% higher than in males. At the same time, the activity of AST activity in the blood serum of males was 17.4% higher than in young females. The concentration of Ca ions in males was 32.4% higher than in females, and concentration of P, on the contrary, was lower in males. The ratio of Ca to P in the blood of males was 1.57, and in females — 1.30. It was found that the content of total protein in animals increased with age and was the highest in adult red deer. While the concentration of the studied macronutrients (Ca, P, Na, K) had a higher level in the blood of young animals. While the concentration of the studied macronutrients (Ca, P, Na, K) had a higher level in the blood of young animals.